Temporal Changes in Blood Metabolome Among Patients on Hemodialysis - Vida Dehghan Niestanak; Natasha Wiebe; Lun Zhang; David S. Wishart; Marcello Tonelli; Larry D. Unsworth (Kidney International Reports)
Introduction: Hemodialysis (HD) sustains millions of lives but is associated with poor clinical outcomes. Metabolite accumulation undoubtedly accounts for some of the excess morbidity and mortality in this population; specific toxins responsible for this are not well-defined. Methods: This prospective study investigates temporal metabolite changes in adults after HD initiation for 60 months or until death or end of study; patients on home or nocturnal HD, peritoneal dialysis, or with a functioning kidney transplant were censored for follow-up. Overall, 267 participants were selected; however, only 241 of these had required samples for analysis at the baseline, 137 at 6 months, 116 at 12 months, and 43 at 60 months. Samples were taken before HD sessions, 80 metabolites isolated from the serum using methanol were quantified using mass spectroscopy techniques, and their concentrations were regressed onto time and participant, using mixed regression in their natural and natural logarithm units. Results: Despite maintenance HD treatment, 74 quantified metabolites showed that 43 significantly increased and 4 significantly decreased in serum concentration over the study period. Of the 43 metabolites that increased in serum concentration over the study period, 24 have not been associated with kidney failure previously. In post hoc analyses, we found that lower water solubility appeared more likely to exhibit increases of metabolites concentration in blood (P = 0.04). Conclusion: The metabolome of patients with kidney failure on maintenance HD changes significantly over 60 months. Future work on correlating toxins and clinical outcomes is needed to drive the development of technologies that improve blood purification for people with kidney failure.